The toxicity comparison of metformin and its degradant guanylurea through multi-routes exposure experiments using algae and rotifer - Fan Gao; Lingyun Zhu; Fan Zhang; Meng Li; Hairong Lian; Sen Feng; Xinfeng Cheng; Xianling Xiang (Ecotoxicology and Environmental Safety)
Metformin (MET) and its metabolite guanylurea (GUA) are prevalent in aquatic environments, raising concerns about their potential risks to aquatic organisms. However, the toxicity of these compounds through different exposure routes has not been reported. This study evaluated the effects of MET and GUA on the growth of the green algae Tetradesmus obliquus and on life table parameters of the freshwater rotifer Brachionus calyciflorus through various exposure routes, including waterborne, foodborne, and combined waterborne + foodborne. Our results indicated that both MET and GUA, at concentrations of 1 mg/L and 100 mg/L, inhibited algae growth, with GUA causing greater stress than MET. Additionally, compared to waterborne exposure, foodborne and combined waterborne + foodborne exposures of MET and GUA at these concentrations significantly decreased the net reproductive rate (R0), intrinsic rate of population increase (rm), and life expectancy (e0) of B. calyciflorus. Notably, the impact of exposure routes on the life table parameters of B. calyciflorus was generally greater than the impact of exposure concentrations. Therefore, previous studies focusing solely on waterborne exposure may have underestimated the toxicity of MET and GUA.